1986
DOI: 10.1007/bf02346056
|View full text |Cite
|
Sign up to set email alerts
|

Mead production by continuous series reactors using immobilized yeast cells

Abstract: Summary. Two series reactors separately packed with immobilized cells of Saccharomyces cerevisiae BRL-7 producing alcohol and Hansenula anomala producing ethyl acetate were used to produce meads of controlled quality. The rate of alcohol production and the amount of ethyl acetate produced were 6.13 g/h and 61.6 mg/100 ml, respectively, at a dilution rate of 1.36 h-1. Coimmobilized cells of S. cerevisiae BRL-7 and H. anomala produced alcohol at the rate of 8.02 g/h with 40 mg/100 ml ethyl acetate content at a d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
8
0

Year Published

1987
1987
2017
2017

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 17 publications
(8 citation statements)
references
References 5 publications
0
8
0
Order By: Relevance
“…Qureshi and Tamhane () produced mead by immobilized cells of Hansenula anomala in calcium alginate gels. Continuously operated column reactors enabled the quick production of matured mead by a single culture and the elimination of the traditionally‐used long ageing periods.…”
Section: Case Studies: Honey Fermentationmentioning
confidence: 99%
“…Qureshi and Tamhane () produced mead by immobilized cells of Hansenula anomala in calcium alginate gels. Continuously operated column reactors enabled the quick production of matured mead by a single culture and the elimination of the traditionally‐used long ageing periods.…”
Section: Case Studies: Honey Fermentationmentioning
confidence: 99%
“…Cell immobilisation also allows easier handling of the cells and facilitates the clarification of the final product (Kocher et al, 2006;Kostov, Angelov, Mihaylov, & Poncelet, 2010;Kourkoutas et al, 2004;Park & Chang, 2000). Studies with immobilised cells in Ca-alginate (Qureshi & Tamhane, 1986) or pectate (Navrátil et al, 2001) in mead production have showed that fermentation length was reduced or fermentation rate increased, respectively. Therefore, the purpose of this study was to evaluate the effect of the yeast cell immobilisation of two yeast strains (QA23 and ICV D47) in a fed-batch system.…”
Section: Introductionmentioning
confidence: 99%
“…In the past few years, several studies on the optimization of mead production have been carried out, mainly regarding yeast selection and honey‐must formulation . However, it is worth noting that immobilized cells were used in just two of the studies involving mead production .…”
Section: Introductionmentioning
confidence: 99%